The Chinese model of development and its experience for Kazakhstan (Journal of Oriental Studies, 2019)
This article analyzes the nature, characteristics and prospects of the development of socialism withChinese characteristics. The theoretical and practical essence of the development of socialism in Chinaand the true nature of modern Chinese socialism for the realization of national revival and the creationof a just and universal rich society are also determined.Key words: Datong, Chinese socialism, modernization, xiaokang, middle-income society (xiaokangshehui),society of universal prosperity (Fuyishehui), Asian values.